First observations of oblique ionospheric sounding chirp signal in Mexico - Sergeeva, Maria A.; Gonzalez Esparza, J. Americo; Blagoveshchensky, D. V.; Maltseva, O.A.; Chernov, A. G.; Corona Romero, Pedro; De la Luz, Victor; Mejía Ambriz, Julio C.; González, L. Xavier; Romero Hernández, Esmeralda; Rodríguez Martínez, Marisol; Aguilar Rodriguez, Ernesto; et al. (Elsevier, 2019)
The results of the first experiment of oblique ionospheric sounding (OIS) chirp signal reception in Mexico are reported. Maximal and Lowest Observed Frequencies variations were studied under the quiet Space Weather conditions. The diurnal ionospheric variations by OIS signal confirm the results based on GNSS data in the Mexican region. The best HF radio propagation conditions along the considered path are during morning and daytime hours. The multi-hop propagation is frequent. The interlayer propagation modes are present at nighttime.